Prophylactic Effect of Chloroquine and Hydroxychloroquine on COVID-19 Treatment - Amin Ataie; Razieh Mansouri; Hossein Khaleghzadeh-Ahangar; Ramin Ataee; Fatemeh Alibabaei (Mazandaran University of Medical Sciences, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly transmissible and pathogenic coronavirus that emerged in late 2019 and has caused a pandemic of acute respiratory disease, named 'coronavirus disease 2019' (COVID-19), which has threatened human health and public safety. Objectives: Hydroxychloroquine (HCQ) is an anti-malaria drug with controversial antiviral properties. Some in vitro studies have approved its antiviral effects. Many efforts have been made to prevent and treat COVID-19, but effective drugs for complete eradication of COVID-19 have not been found yet and all available drugs are supportive.  Methods: We tried to review some new aspects of HCQ efficacy in the prevention and treatment of COVID-19 infection. Also, some data from recent clinical trials were studied. It has been shown that HCQ may improve some symptoms of patients, but in severe or critical stages, it did not have significant therapeutic effects and did not reduce the rate of mortality. Results: In this review article, we explained some results of recent studies, including clinical trials on the effects of HCQ on the prevention and treatment of COVID-19 infection. Some studies have revealed HCQ's beneficial effects in outpatients, and some data showed its hazardous impacts on the heart. The available evidence suggests that CQ or HCQ does not improve clinical outcomes in COVID-19. Well-designed randomized trials are required for assessing the efficacy and safety of HCQ and CQ for COVID.  Conclusion: It was suggested that the dose of HCQ administration must be adjusted and monitored correctly; furthermore, the levels of some myocardial biomarkers, such as troponin must be measured in mild to moderate, severe, and critical infection. Also, combination therapy with other drugs, such as azithromycin may have better anti-inflammatory and antiviral effects.